Technology Transfer and the Promotion of Technical Skills from Japan to Southeast Asia: Case Study of Vietnam - Quynh Huong Nguyen (JAS (Journal of ASEAN Studies), 2018)
In this era of globalization, technology transfer is widely regarded as a significant vehicle by which developing countries can both acquire technologies and develop human resources. Also, the skills level of employees has been identified in playing a critical role in making technology transfer effective. Japan is one of the largest investors in Vietnam. Japanese foreign direct investment (FDI) projects that are large in terms of investment capital and concentrate in high technology industries, are predicted to continue to increase and they offer the promise of new employment and technology transfer opportunities for Vietnam and its people. However, the lack of a skilled labor force in Vietnam, especially in the manufacturing industry, has currently impeded the transfer of technologies from Japan to Vietnam. Human resource development in general and technical skill promotion in particular are critical requirements for Vietnam to take advantage of technology transfer.This paper attempts to evaluate the current situation of technical skill levels of employees in the Vietnamese manufacturing industry, as well as technology transfer from Japan to Vietnam through Japanese FDI manufacturing firms. In addition, this paper introduces the current policies and strategies of the Vietnam government in relation to technology transfer issues. It is suggested in this paper that bridging the huge gap between Japanese technical standards and the Vietnamese workforce’s technical skills definitely requires the crucial role of the Vietnamese government. The author then provides some recommendations for the government to adopt in order to upgrade technical skill levels to effectively adopt and utilize technologies transferred from Japan in the manufacturing industry.